2005
DOI: 10.1308/003588405x51074
|View full text |Cite
|
Sign up to set email alerts
|

Management of suspected scaphoid fractures in accident and emergency departments – time for new guidelines

Abstract: INTRODUCTION The objectives of this work were to assess the clinical knowledge of clinicians in the accident and emergency (A&E) departments in England & Wales and evaluate the current trend for the acute management of radiologically normal, but clinically suspected, fractures of the scaphoid.SUBJECTS AND METHODS We conducted a telephone survey on 146 A&E senior house officers (SHOs) in 50 different hospitals. This survey assessed the clinicians' experience, their clinical and radiological diagnostic methods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…There was only one confirmed scaphoid fracture in the total study population (demonstrated in the MRI group) and a total of 4 fractures, suggesting 75% of patients in this study were needlessly immobilised. These results mirror other studies, which suggest that the prevalence of true fractures is low 8, 10. MRI also detected other injuries outside of the scaphoid that may go undetected using conventional management techniques.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…There was only one confirmed scaphoid fracture in the total study population (demonstrated in the MRI group) and a total of 4 fractures, suggesting 75% of patients in this study were needlessly immobilised. These results mirror other studies, which suggest that the prevalence of true fractures is low 8, 10. MRI also detected other injuries outside of the scaphoid that may go undetected using conventional management techniques.…”
Section: Discussionsupporting
confidence: 86%
“…A clinically important proportion of scaphoid fractures are not demonstrated on a radiograph immediately after injury. Several authors have suggested that fractures of the scaphoid are occult in about 16% of cases on initial radiographs 8, 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of injury also accounts for accounts for 1:10,000 attendances annually in Uk Emergency Departments (UK) (Tai, 2005). Between 5 -12 % of scaphoid fractures are related to other fractures (Malik et al, 2010).…”
mentioning
confidence: 99%